2019
DOI: 10.1063/1.5114695
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation quenching and phase-flip bifurcation in coupled thermoacoustic systems

Abstract: Oscillatory instabilities, although ubiquitous in nature, are undesirable in many situations such as biological systems, swaying of bridges and skyscrapers, aero-acoustic flutter, prey-predator and disease spread models, and thermoacoustic systems, where they exhibit large amplitude periodic oscillations. In the present study, we aim to study the suppression mechanism of such undesired oscillations in a pair of thermoacoustic oscillators, also known as horizontal Rijke tubes. These oscillators are coupled thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
2
50
0
Order By: Relevance
“…3 and 4 bear some similarity to the studies found in Refs. [33,67,100] where phase-flip bifurcations are studied. The difference is that the referenced works consider transient bifurcations which occur during operation as some parameter is varied, while our investigation is focused on steadystate phenomena with all parameters constant during operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4 bear some similarity to the studies found in Refs. [33,67,100] where phase-flip bifurcations are studied. The difference is that the referenced works consider transient bifurcations which occur during operation as some parameter is varied, while our investigation is focused on steadystate phenomena with all parameters constant during operation.…”
Section: Discussionmentioning
confidence: 99%
“…[29]. We also mention that nonlinear phenomena in can-annular configurations, such as amplitude death and quenching, have drawn increased interest in recent years [30][31][32][33].…”
Section: Thermoacoustic Instabilities In Can-annular Combustorsmentioning
confidence: 99%
“…Using similar concepts, Dange et al. (2019) observed experimentally in-phase/anti-phase synchronization, phase-flip bifurcations and partial amplitude death in two coupled Rijke tubes powered by electric heaters. Similarly, Biwa, Tozuka & Yazaki (2015), Hyodo & Biwa (2018) and Hyodo, Iwasaki & Biwa (2020) observed experimentally in-phase/anti-phase synchronization and amplitude death in two coupled thermoacoustic oscillators powered by electric heaters and laminar Bunsen flames.…”
Section: Introductionmentioning
confidence: 96%
“…They also confirmed that AD can be observed even in situations where white noise is applied [32]. Dange et al experimentally examined AD in coupled Rijke tube oscillators [33]. Hyodo et al experimentally confirmed the effectiveness of multiple delayed connections in coupled Rijke tube oscillators [34].…”
Section: Discussionmentioning
confidence: 83%